Selection Pressure Pathways and Mechanisms of Resistance to the Demethylation Inhibitor-Difenoconazole in Penicillium expansum - Ali, Emran Md; Amiri, Achour (Frontiers in Microbiology, 2018)
Penicillium expansum causes blue mold, the most economically important postharvest disease of pome fruit worldwide. Beside sanitation practices, the disease is managed through fungicide applications at harvest. Difenoconazole (DIF) is a new demethylation inhibitor (DMI) fungicide registered recently to manage postharvest diseases of pome fruit. Herein, we evaluated the sensitivity of 130 P. expansum baseline isolates never exposed to DIF and determined the effective concentration (EC50) necessary to inhibit 50% germination, germ tube length, and mycelial growth. The respective mean EC50 values were 0.32, 0.26, and 0.18 µg/ml indicate a high susceptibility of P. expansum baseline isolates to DIF supported by a full and extended control efficacy in vivo after 6 months of storage at 1°C. We conducted a risk assessment for DIF-resistance development using ultraviolet excitation combined with or without DIF-selection pressure to generate and characterize lab mutants. Fifteen DIF-resistant mutants had EC50 values of 0.92 to 1.4 µg/ml and 1.7 to 3.8 µg/ml without and with a DIF selection pressure, respectively, and resistance was stable in vitro over a 10-week period without selection pressure. A tyrosine to phenylalanine mutation was found at codon 126 (Y126F) of the CYP51 gene in all of the 15 mutants but absent in the wild-type parental isolates of P. expansum. Resistance factors increased 5 to 15-fold in the mutants compared to the wild-type -isolates. DIF-resistant mutants also displayed enhanced CYP51 expression by 2 to 14-fold and was positively correlated with the EC50 values (R2 = 0.8264). No-cross resistance was observed with the mixing-partner fludioxonil. Our findings suggest P. expansum resistance to DIF is likely to emerge in commercial packinghouse once used frequently. Future research is need to investigate if DIF-resistance is qualitative or quantitative which will be determinant in the speed at which resistance will develop and spread in this pome fruit-Penicillium pathosystem and to develop appropriate strategies to preserve the lifespan of this new fungicide.